Metode Pembelajaran Bahasa Jepang Tingkat Dasar Berbasis Multimedia Menggunakan Macromedia Flash Mx - Sapri, Sapri; Kanedi, Indra (Jurnal Media Infotama, 2020)
Multimedia-Based Elementary Level Japanese Language Learning Method Using Macromedia Flash MX (2010). This research aims to create a basic level Japanese language learning method at LP2M El Rahma Bengkulu using Macromedia Flash MX, to make it easier for teachers, pupils and students to learn basic level Japanese so as to increase interest and attraction in learning Japanese. The research was carried out at LP2M El Rahma Bengkulu, whose address is Jalan Kemang Manis No.10 Sawah Lebar Bengkulu Tel. (0736) 22123 Bengkulu. The research was carried out from March to July 2010. The problem in this research is how to create a basic level Japanese language learning method using Macromedia Flash MX. So it can be useful for El Rahma Bengkulu and students of course. Based on the results and discussion as well as the results of system testing, it can be concluded that in creating this Japanese language learning method at LP2M El Rahma Bengkulu, they first created a system design. This software was created using Macromedia Flash MX. So it has an attractive appearance and gets good results.